PENGARUH KOMUNIKASI INTERNAL, BUDAYA ORGANISASI DAN LOYALITAS TERHADAP KINERJA KARYAWAN PERUMDA BANYUMILI KAB. REMBANG - Yolva Aulia Putri; Anik Nurhidayati (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This research aims to examine the influence of internal communication, organizational culture, and loyalty on employee performance at Perumda Air Minum Banyumili, Rembang Regency. The study used a quantitative survey-based method involving 90 employees as respondents. The research instrument was a Likert-scale questionnaire consisting of 47 statement items covering four variables. The collected data were then analyzed using multiple linear regressions, supplemented by instrument testing and general assumption testing to ensure the feasibility of the model. The results of the study revealed that internal communication significantly influences employee performance, indicating that a clear flow of information and effective communication patterns support improved work quality. Organizational culture was also proven to have a positive and significant impact, so that ingrained values, rules, and work ethics are able to shape employee attitudes and work actions optimally. Meanwhile, loyalty has a positive, although not significant effect on performance. The R-square value of 0.488 provides evidence that the three variables together explain 48.8% of the difference in employee performance. This study recommends improving communication systems, strengthening organizational culture, and loyalty development strategies to improve employee performance sustainably.